European cities modernity, race and colonialism - Ha, Noa; Picker, Giovanni (Manchester University Press, 2022)
European cities: Modernity, race and colonialism is a collection of empirical and theoretical scholarly analyses of multiple urban processes across the East-West European divide, inviting the reader to reimagine urban Europe from non-Eurocentric perspectives, and to engage active thought and thoughtful action.